PERAN CITRA PERUSAHAAN, KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP MINAT BELI ULANG PADA KONSUMEN ASTON PLUIT HOTEL & RESIDENCE DI JAKARTA - Heridiansyah, Jefri; Christiana, Anya Aprillia; Wahyudi, Wahyudi; Setiyanti, Sri Wiranti (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to determine the influence of company image, service quality and price perception on repurchase intention among Aston Pluit Hotel & Residence consumers in Jakarta. The sampling technique used is probability sampling with the technique taken being accidental sampling. The results of the t test show that the t value for company image is 7.868 > t-table 1.984, then the t value for service quality is 2.838 > t-table 1.984 and the t value for price perception is -1.960 < t-table 1.984. The results of testing the feasibility of the model with a significant level are 0.000 < 0.05, meaning that the model is a suitable model or fit to be used. The coefficient of determination (Adjusted R Square) of 0.863 means that repurchase interest can be explained by company image, service quality and price perception.